Stability of Electrode Materials During Electrolysis in LiCl-KCl Melt - Kim, Dae-Hyeon; Bae, Sang-Eun; Park, Tae-Hong; Song, Kyuseok; Choi, Jong-Ho (Asian Journal of Chemistry, 2014)
Tungsten, molybdenum and carbon were tested for the electrodes in LiCl-KCl melt at 450 °C using electrochemical and scanning electron microscopic techniques. Open circuit potentials for the W and Mo electrodes were stabilized near -0.23 and -0.41 V, respectively while that of the carbon electrode is slowly shifted from 0 to -0.33 V. Cyclic voltammetry and SEM results show that the metal electrodes can be corroded in an anodic potential range. The carbon electrode was stable at a potential more positive than -1.0 V but became coarse at a more negative potential. Using these results, the electrode materials were evaluated for usage in LiCl-KCl melt and relatively stable electrode materials for the pyrochemical process were suggested.